Affinity-purified antibodies to ring-infected erythrocyte surface antigen do not correlate with merozoite invasion inhibition in Plasmodium falciparum. - Coleman, J P (1988)
We affinity purified, from malaria-immune serum, antibody to the ring-infected erythrocyte surface antigen (RESA), using petri dishes containing a monolayer of Plasmodium falciparum ring-infected erythrocytes. Except for one out of eight samples, the purified antibody positive by RESA-immunofluorescent assay was not inhibitory to the in vitro invasion of merozoites into erythrocytes in three geographically distinct strains of P. falciparum. However, the initial high level of merozoite-inhibiting antibodies of the intact serum samples remained in the immunoglobulin G fraction from which the RESA antibodies had been removed by affinity chromatography. These results suggest that, although in some cases RESA-immunofluorescent assay-positive antibodies may be inhibitory to merozoite invasion, there are more important antibodies capable of merozoite invasion inhibition.